Pengembangan Media Pembelajaran Flash Berbasis Joyfull Learning bagi Siswa Kelas IV SD - Azhar, Arry Patriasurya; Rahayu, Zaenab Fuji (JURNAL PENDIDIKAN DASAR NUSANTARA, 2021)
This study aims to determine the feasibility of flash learning media products based on joyful learning for fourth grade students, namely science learning with the subject of "Gaya" Theme 7 (Beautiful Diversity in My Country). This study uses the research and development (R&D) method. The model used refers to the Dick & Carey model which consists of eight stages. Results of this study indicate that the developed joyfull learning-based flash learning media can meet learning needs of students, as well as increase the variety of teaching media in the science learning process with subject "Gaya" Theme 7 (Beautiful Diversity in My Country). This is based on the results of validation test: (1) media product expert with a very good score; (2) material expert with good scores; (3) classroom teachers with very good grades. As for the individual trial stage, an average score of 4.1 was obtained (good), while small group trial with an average value of 4.6 (very good), and large group trial obtained an average value of 4,1 (good). Keywords: Learning media, joyful learning, multimedia, flash